Gambaran Faktor-Faktor Yang Mempengaruhi Demam Berdarah - ebu, fahira; Febrianti, Nur; R, Rabiah; I, Iwan (An Idea Nursing Journal, 2022)
This research is a descriptive research. The population is all respondents who have been exposed to dengue fever in the work room of UPTD Birobuli opening 31 respondents and the testing method using a complete population of 31 respondents using polls. The examination used is Univariate Analysis. The results showed that the distribution of the 31 respondents studied showed that the distribution based on respondents' knowledge about Dengue Fever was poor knowledge, namely 20 respondents with a percentage (64.5%) while good, namely 11 respondents with a percentage (35.5%), and also the distribution of respondents based on the habit of hanging clothes is not good 23 respondents with a percentage (74.2%), and good, namely 8 respondents with a percentage (25.8%). The lower the level of the school, the lower the understanding and knowledge, this is influenced by the approach, depending on the habit of being exposed to dengue fever, this is influenced by age. Based on the habit of hanging clothes, most of them are not good.